A KPI Based Performance Assessment System - Mahmud, Israt (2009)
Employee performance evaluation is an effective way to determine the ranking of the employees in an organization. Key Performance Indicators (KPI) is quantifiable measurements that reflect the significant success factors of an organization. They will differ depending on the organization. In this proposal a web-based performance evaluation system using predetermined KPI is being proposed, which provides a secure and easy way to conduct the assessment specifically of the UUM academic staffs. This system will be integrated to the other existed system of UUM to extract the required information. Prototyping approach was adopted as the development method of this proposed system.